The legitimacy of the Tibetan Government in Exile - Mitko, Marta (Riga Graduate School of Law, 2020)
The paper examines the legitimacy of the Tibetan Government in Exile as the establishments of democratic governing system, consisting of all three pillars, undeniably prove the state of law created within the community and fulfilling all the state-like functions. The legal basis of this paper fall under the scope of international law and the principle of recognition of both governments (in situ and in exile) and states. The aim is to prove the state of law within the TGiE and successful functioning as the representative of Tibetan people, thus presenting the continuity of state that is dating back to the de facto independence from 1913 to 1951 and the safeguarded state’s personality that still is not legally recognized. The mere reason of such non-recognition of the TGiE can be explained by the sole fact of the lack of the de jure recognition.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; State recognition